PENYIDIKAN TINDAK PIDANA KARTU KREDIT OLEH DIREKTORAT RESERSE KRIMINAL KHUSUS KEPOLISIAN DAERAH RIAU - Wedy Freddy Santoso; Firdaus '; Erdiansyah ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Crime in human life is a social phenomenon that will always be faced by every human being, society, and even countries. The fact has proved that crime can only preventable and mitigated but difficult to eradicated completely. This research can be classified in this type of sociological juridical research. This research was conducted at the Police Ditreskrimsus of Riau area, while the population and sample is a whole part with regard to the issues examined in this study, the data source used, primary data, secondary data, and the tertiary data, data collection techniques in this research is by the interviews , and literature study. Analysis of the data used is qualitative data and techniques by means of deductive inference.From the results of the research obtained can be concluded. First, in handling criminal case of credit card the Riau Police conduct inquiry and investigation, make coordination with various parties, reviewing and evaluate the progress of crimes using computers and make the prediction of developments that will happen. Second, the constraints faced is the limited number of personnel, facilities and infrastructure in the inquiry and investigation, the cooperation between law enforcement agencies is still to be casuistry, and the public was slow to report the incident to the authorities so that it can complicate the process of evidence. Third, the efforts of the regional police of Riau is the effort Preventive do the counseling and introduce to the publics some of the operation modus of the perpetrators of the Crime of Credit Card, Repressive efforts implemented through the actions expressly and in accordance with the legislation in force against the perpetrators of crimeKeywords: Law Enforcement-Crime-Credit Cards